Lipid analysis of developing Camelina sativa seeds and cultured embryos. (October 2015) - Pollard, Mike; Martin, Tina M.; Shachar-Hill, Yair
Graphical abstract: Camelina sativa seed development in silique and the culture of developing embryos were compared with respect to lipid deposition. Fatty acid, triacylglycerol and lipid class analyses were optimized to resolve and identify minor components. Highlights: Fatty acid content and composition measured over Camelina seed development. Lipid accumulation during development compared for seeds and embryo culture. Identified 15, 16-epoxy- and 15-hydroxy-linoleate, and C20–C24 hydroxy fatty acids. Identified triacylglycerols containing epoxy and hydroxy fatty acids. Optimized lipid analysis methods for Camelina seed lipid research. Abstract: Camelina sativa is a cultivated oilseed rich in triacylglycerols containing oleic, linoleic, α-linolenic and eicosenoic acids. As it holds promise as a model species, its lipid synthesis was characterized in vivo and in culture. Lipid accumulates at a maximum rate of about 26 μg/day/seed (11.5 mg lipid/day/g fresh seed weight), a rate comparable with other oilseeds. Noteworthy is a late stage surge in α-linolenic acid accumulation. Small amounts of unusual epoxy and hydroxy fatty acids are also present in the triacylglycerols. These include 15, 16-epoxy- and 15-hydroxy-octadecadienoic acids and homologous series of ω7-hydroxy-alk-ω9-enoic and ω9/10-hydroxy-alkanoic acids. Mid-maturation embryos cultured in vitro have growth and lipid deposition rates and fatty acid compositions that closely match that of seeds, but extended culture periods allow these rates to rise and surpass those observed in planta . Optimized thin layer chromatography systems for characterization of labeled products from acetate or glycerol labeling are described. Glycerol label is only found in acylglycerols, largely as the intact glyceryl backbone, but acetate can label acyl groups and sterols, the latter to a much higher relative specific activity. This presumably occurs because mevalonic acid precursor is derived from the non-plastid pool of acetyl-CoA that is also the source for malonyl-CoA to drive FAE1-dependent chain elongation. Particular attention has been paid to the separation of sterols and diacylglycerols, and to hydrogenation of triacylglycerols to simplify their analysis. These improved methods will allow more accurate analyses of the fluxes of lipid metabolism in cultured plant embryos.